HUBUNGAN PENGETAHUAN, SIKAP DAN PERILAKU PENDAKI GUNUNG DALAM PENGELOLAAN SAMPAH (STUDI KASUS DI GUNUNG PRAU, KABUPATEN WONOSOBO) - Elisabeth Deta Lustiyati; Royan Stulasyqin Fadli; Theresia Puspitawati (Jurnal Belantara, 2022)
Mount Prau ecotourism is one of the tourist objects in the Dieng highland area, Wonosobo. The increase in climbing tourists from year to year has a significant impact on the generation of waste at Mount Prau basecamp. Waste management includes waste minimization and handling practice. Climbers' knowledge for reducing and handling waste during climbing as well as attitudes in waste management is important in reducing waste generation. This study aims to determine the relationship between knowledge, attitudes, and behavior of mountain climbers in waste management. The type of research is an observational analytic study with a cross-approach design. The research technique used survey methods, interviews, questionnaires, and observations. This study involved 159 respondents to fill out a questionnaire containing 30 questions about the knowledge, attitudes, and behavior of waste management. Data analysis used the Spearman correlative test with a significance level of 5%. Based on the data analysis, it was found that there was a positive and significant relationship between knowledge and behavior (p = 0.014, Rs = 0.194), as well as the results on the attitude and behavior variabels (p = 0.013, Rs = 0.197). The conclusion of this study the better the climber's knowledge and attitude towards waste reduction and handling, the better the waste management behavior of the climbers